Bezbariérový dům - Michl, Miroslav (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Předmětem bakalářské práce je návrh novostavby bezbariérového rodinného domu na úrovni projektové dokumentace ve stupni pro provedení stavby. Objekt je nepodsklepený, s jedním nadzemním podlažím se stěnovým konstrukčním systémem z cihelných bloků, založen na betonových základových pasech a zastřešen plochou střechou. Návrh domu klade důraz na dispoziční řešení pro osobu s omezenou schopností pohybu a její samostatnost při užívání, včetně zajištění konstrukce po stránce statické, architektonické, úspory energie a bezpečnosti při užívání objektu.

The aim of bachelor’s thesis is a project of new detached barrier-free house at a level of project documentation for the building realization. The building object is without basement and with one above-ground floor with wall construction system from brick blocks founded on strip foundations from concrete and covered with a flat roof. The building project is completed in accordance with design requirements for building typology of barrierless buildings and access for disabled person and for her self-reliance while using, including design of building constructions and materials in terms of statics, architecture, evaluation of thermal protection of the building envelope and safety while using.
Barrierless house
Keywords: Bezbariérový dům; rodinný dům; jednopodlažní dům; stěnový konstrukční systém z cihelných bloků; plochá střecha; bezbariérové bydlení pro osoby s omezenou schopností pohybu; Barrier-free house; detached house; single-storey house; wall construction system from brick blocks; flat roof; barrierless building for disabled people